IDENTIFYING ISLAMIC VALUES ON GREEN ARCHITECTURAL CONCEPT: QUANTITATIVE APPROACHES TO CONTENT ANALYSIS - Muchlis, Aulia Fikriarini; Larasati, Dewi; Triyadi, Sugeng (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2019)
The paper investigates to explore Islamic religious values which related to environment Maintaining environmental balance is the primary human task. Besides, religious belief is a source of ethics and morality. It is a guidance of truth for making decisions before taking action influencing humans’ behavior towards perceptions and behavior in maintaining and preserving their environment. This study employs a quantitative approach by conducting a content analysis aiming to understand every word (text) related to land, water, and air through the interpretation of the Quran. This research will produce several criteria as the basic concepts for the development of Islamic values-based green architecture.